THE EFFECT OF USING SAGU DRUGS (Metroxylon sagu) AND DRIED BANANA LEAVES (Musa paradisiaca) ON THE GROWTH OF WHITE OYSTER MUSHROOM (Pleurotus ostreatus) - Rahmatan Islami; Eva Nauli Taib; Zuraidah Zuraidah (Universitas Islam Negeri Ar-Raniry, 2024)
Oyster mushrooms (Pleurotus ostreatus) are wood fungi that grow sideways on rotting wood stems. Mushrooms take food that has been made by other dead organisms (saprophyte), because they do not have chlorophyll, all types of saprophyte, especially those that grow on wood, can be easily cultivated. White oyster mushroom cultivation is easy to do because it does not require expensive maintenance costs and does not require spacious land. The aim of this research was to test the effect of using sago dregs and dried banana leaves on the growth of white oyster mushrooms. The results of this research indicate that there are differences in the growth of white oyster mushrooms based on different concentrations of growing media. The average mycelium growth, stem height, pileus diameter, number of fruit bodies, wet weight and dry weight of the best white oyster mushrooms were found in media with a concentration of 100% sawdust, while pind heads appeared in a concentration of 100% sago dregs